Co-producing active lifestyles as whole-system-approach: theory, intervention and knowledge-to-action implications. (8th September 2017) - Rütten, Alfred; Frahsa, Annika; Abel, Thomas; Bergmann, Matthias; de Leeuw, Evelyne; Hunter, David; Jansen, Maria; King, Abby; Potvin, Louise
Abstract: Population health interventions tend to lack links to the emerging discourse on interactive knowledge production and exchange. This situation may limit both a better understanding of mechanisms that impact health lifestyles and the development of strategies for population level change. This paper introduces an integrated approach based on structure-agency theory in the context of 'social practice'. It investigates the mechanisms of co-production of active lifestyles by population groups, professionals, policymakers and researchers. It combines a whole system approach with an interactive knowledge-to-action strategy for developing and implementing active lifestyle interventions. A system model is outlined to describe and explain how social practices of selected groups co-produce active lifestyles. Four intervention models for promoting the co-production of active lifestyles through an interactive-knowledge-to-action approach are discussed. Examples from case studies of the German research network Capital4Health are used to illustrate, how intervention models might be operationalized in a real-world intervention. Five subprojects develop, implement and evaluate interventions across the life-course. Although subprojects differ with regard to settings and population groups involved, they all focus on the four key components of the system model. The paper contributes new strategies to address the intervention research challenge of sustainable change of inactive lifestyles. The interactive approach presented allows consideration of the specificities of settings and scientific contexts for manifold purposes. Further research remains needed on what a co-produced knowledge-to-action agenda would look like and what impact it might have for whole system change.